Mechanically robust and self-cleanable encapsulated metalens via spin-on-glass packaging - Younghwan Yang; Dohyun Kang; Junhwa Seong; Kyungtae Kim; Seokwoo Kim; Chunghwan Jung; Eunji Lee; Hyeonsu Heo; Hyunjung Kang; Nara Jeon; Jihae Lee; Youngsun Jeon; et al. (Microsystems & Nanoengineering)
Abstract Metalenses—two-dimensionally arranged artificial nanostructures that focus light—have been extensively studied due to their great potential for applications in consumer goods and industrial products. However, when metalenses are exposed to harsh environments, they can suffer from mechanical shocks and damage, leading to degradation in optical performance. Here, we present mechanically robust and self-cleanable encapsulated metalenses using spin-on-glass coatings on structured hydrogenated amorphous silicon (a-Si:H), whose optical properties are optimized for effective waveguiding. The atomic structure of a-Si:H has been precisely engineered to achieve a high refractive index (3.23) with near-zero optical losses at the wavelength of 635 nm by adjusting deposition parameters. We develop an analytical model to determine how the refractive index of nanostructures influences light manipulation, highlighting the correlation between refractive indices of structures and metalens efficiencies. Using the high refractive index of the a-Si:H, our encapsulated metalenses achieved a calculated conversion efficiency of 97.2% at the wavelength of 635 nm. Additionally, we verify their mechanical robustness by sonicating encapsulated metalenses with sand for 120 min, demonstrating strong mechanical durability. Furthermore, with the capability of the encapsulated metalenses to perform self-cleaning, this work paves the way for practical applications of metalenses in diverse environments.